Study of the effect of selenium application on seed germination and initial growth of seedlings of three medicinal plants of dragons head, alyssum and chicory under salt stress - Masoomeh Amerian; Ali Reza Khosravi (علوم و فناوری بذر ایران)
In order investigate the effect of salinity and selenium on seed germination of three medicinal plants dragons head, alyssum and chicory, this study was performed as a factorial experiment based on a complete randomized design with two factors including different levels of salinity and selenium in three replications. The first factor included 0, 2, 4, and 8 mM NaCl and the second factor was 0, 5, 10, and 20 mg L-1 sodium selenate levels. Unlike selenium, salinity reduced germination percentage, germination characteristics and initial growth in all three medicinal plants. The germination percentage of chicory was 40%, alyssum was 49.1% and dragons head was 52.5%, which indicates that chicory is more sensitive to salinity stress, while dragons head showed more tolerance to salinity stress. With increasing selenium concentration, seedling length in all three medicinal plants increased compared to the control. The highest seedling length (20 mm) was observed in treatment 20 mg L-1 sodium selenate with a concentration of 8 mM NaCl in alyssum. The lowest seedling length was in chicory (6.2 mm) and in 0 mg L-1 sodium selenate treatment with 8 mM NaCl. The use of selenium can improve germination characteristics and to some extent reduce the effects of salinity stress. In general, it can be concluded that selenium (at the level of 20 mg L-1 of sodium selenate) can increase seed germination and seedling growth of all three medicinal plants under salinity stress.